Customer Relationship Management (CRM) Strategies For Enhancing Promotional Effectiveness: A Case Study Of Zakiyah Shop - Era Fazira; William Ramdhan; Akmal (ITEJ (Information Technology Engineering Journals), 2026)
The rapid development of information technology has encouraged businesses to adapt to improve the effectiveness of marketing and customer service. Toko Zakiyah Serba Ada, a retail business specializing in fashion and daily necessities, still faces various challenges, such as manual promotional strategies, limited access to product information, and the lack of an integrated system for managing customer data and promotional activities. These conditions result in low promotional effectiveness and suboptimal customer relationships. This study aims to analyze the implementation of a web-based Customer Relationship Management (CRM) system to support more effective promotional strategies and increase customer loyalty. The research method used is a qualitative method with data collection techniques through interviews, observations, and literature studies. The data used comes from customer transaction history for the period November 2024 to October 2025. The results show that the implementation of a web-based CRM system is able to integrate customer data, transactions, and promotions into one structured system. This system provides various features such as live chat, messages, shopping carts, promotions, and reviews that support two-way interactions between the store and customers. In addition, the CRM system also enables customer behavior analysis so that promotional strategies can be implemented in a more targeted and data-driven manner. The conclusion of this study is that implementing web-based CRM positively impacts the effectiveness of promotional strategies and improves the quality of store-customer relationships. Therefore, a CRM system can be an appropriate solution for facing increasingly competitive business environments in the digital age.